Evaluation of adherence to pharmacological treatment - William Henrique da Silva; Débora Santos Dantas; Baldoíno Sonildo da Nóbrega; Maria do Socorro Ramos de Queiroz; Harley da Silva Alves (Universidade de São Paulo, 2019)
The adherence to therapy associated with the socio-demographic variables and the habits of patients with hypertension and/or diabetes mellitus were investigated in this study. The registration forms of 105 patients in the Hiperdia program in the municipality of Campina Grande-PB were used as a data collection instrument, applying the Morisky-Green test (MGT) and Batalla test (BT) to assess compliance treatment. For the MGT, there was a prevalence of non-adherent individuals (76.2%) and the type of predominant behavior was unintentional. The internal consistency of the responses obtained through the MGT presented good reliability, according to the value of 0.69 obtained by Cronbach's alpha. For the BT, there was a predominance of adherence (68.6%) and the alpha value was 0.80, showing a high reliability level. It was found that a diet lacking in salt is a strong impact variable for determining the adherence to the BT. Given the representativity of the tests, there is a need to amend the interferences that facilitate the low adherence to drug treatment. The results of this study can be used to construct strategies that will address these difficulties and optimize the adherence level and quality of life of patients.